Affine group linear operator-based channel characterization for mobile radio systems - Okonkwo, Uche A. K.; Ngah, Razali; A. Rahman, Tharek (2008)
Mobile radio channel characterization using linear operators of affine group is presented. The foundation of this approach is primarily based on the natural extension of basic concepts of time-scale representations of wavelet-type to the analysis and representation the nonstationarity associated with the real-time mobile radio channel. We provide an operator-based characterization initiated by the need to present an intuitive and physical approach towards describing and representing the various effects of the channel. The concepts of delay-scale spreading function and operator as well as delay-scale scattering function and operator is introduced. We established the relationship between the continuous wavelet transform and these functions/operators by employing the powerful tool of group theory. We also derived canonical expression for the corresponding channel by discretizing the channel using frame concept. The practical relevance of our approach is illustrated via deterministic examples and the associated simulations.